Characterisation and sustainability evaluation of cereals and pulses formal seed production systems in Cameroon - Moise Harnold Fotso Ngangoua; Eric Bertrand Kouam (PLoS ONE, 2025)
Cereals and pulses are essential commodities for human nutrition in Africa. Seed quality is the vital input and precondition for good agricultural production. Good seeds are mainly supplied by the formal system, which is struggling to ensure its sustainability in Africa. Providing solutions to this systemic problem first requires making a diagnosis. This study aims to characterize the cereal and pulse formal seed production system in Cameroon. The study was conducted in the Sudano-Sahelian (SSZ) and Western highlands (WHZ) agroecological zones (AEZs) of Cameroon and consisted of a triangulation of information: (1) documentary research, (2) semi-structured interviews with seed certification managers and, (3) administration of questionnaires to seed producers. Cross-tabulations and chi-square tests revealed a statistically significant differential distribution of many seed system variables between AEZs, botanical category, cereal types, and legume types. Results reveal that seed production activity is strongly dominated by men with however a considerable proportion of women observed in WHZ (23.3%) compared to SSZ (1.5%). In this latter zone, the declared areas are much larger than in WHZ. Therefore, in order to preserve the purity of crops intended to be seeds, spatial isolation (72.2%) is mainly observed in SSZ against temporal isolation (58.1%) in WHZ. Diversity estimates of varieties and species in seed production were significantly higher in SSZ [H’ (variety) =2.86; H’ (species) = 1.68); richness (variety = 25); richness (species) = 6] compared to WHZ [H’ (variety) =2.31; H’ (species) = 1.13); richness (variety = 19); richness (species) = 6]. Seeds are mostly produced in monocropping system in both zones (95% in SSZ and 62% in WHZ) in comparison to intercropping system. Average yields are relatively low in both AEZs (1 to 2 t/ha for cereals and less than 32 1 t/ha for pulses). Although the low yield coupled with the unsold of all the seeds produced during the cropping season weakens the production system, the marked diversity observed in both AEZs is important for strengthening the sustainability of the seed production system in Cameroon.